Works in progress: new technologies and the European Court of Human Rights - Murphy, Thérèse; Ó Cuinn, Gearóid (Oxford University Press, 2010)
A field—new technologies and human rights or, more broadly, law and technology—is in the process of being framed. Should the European Court of Human Rights be seen as part of that process? To find out, we searched the Court’s case-law using HUDOC, a database on the Council of Europe website which contains both judgments and admissibility decisions. We entered 155 keywords, all in English, and in this article we report and analyse what we found. The overall conclusion is twofold: first, it is too early to attempt a complete characterisation of the Court’s position on new technologies; and second, the Court is however ‘one to watch’.